Aesthetic Judgement and Visual Impact of Architectural Forms: A Study of Library Buildings. (2016) - Jennath, K. Aysha; Nidhish, P.J.
Abstract: Aesthetic appeal of a building, in architecture, has a key concern and isgenerally adjudged a subjective feature. Yetsome buildings are appreciated worldwide, while some others are criticised. Possibilities are there that certain built form characteristics exist, which make buildings appeal to the mass. This study attempts to realise those intentionally or intuitively used parameters for the aesthetic appraisal of a building's external form. Various buildings were examined and form featuresanalyzed so as to find out which makes them aesthetically appealing and howan external form affects the assessment of internal space quality. A survey was conducted among an identified user group; herecollege students, to evaluate the aesthetic appeal of certain selected public buildings; here library buildings, to rate how the building satisfies certain chosen qualities and the expected functionality. The data obtained indicates that there exist certain built form features preferred by the present community and that building aesthetic appeal and expected functionality shows a high positive correlation.